A proposed work-oriented program for the National Training School for Girls Marillac Hills - Perez, Teresita Casaclang 1932- (1974)
A therapeutic school program which makes use of work-oriented experiences is proposed in the study to normalize the deliquent and emotionally disturbed girls at the National Training School for Girls. Besides the therapeutic value of work, this study expounds on the value and importance of therapeutic education and the therapeutic teacher. Several school programs are proposed from which the teachers can select the best time schedule that will serve the needs and interests of the girls. Included in the study are recreation and athletic programs which the teachers can alternate with the work program
Vita.
Thesis (M.A.T. Special Education-Behavioral Problems)--University of the Philippines, Diliman.
Keywords: Girls' schools -- Alabang (Muntinlupa City).; Curriculum planning -- Philippines -- Alabang (Muntinlupa City).; Rehabilitation centers -- Philippines -- Alabang (Muntinlupa City).